2004
DOI: 10.1007/s00468-004-0345-8
|View full text |Cite
|
Sign up to set email alerts
|

Carry-over effects of ozone and water stress on leaf phenological characteristics and bud frost hardiness of Fagus crenata seedlings

Abstract: We examined the carry-over effects of ozone (O 3 ) and/or water stress on leaf phenological characteristics and bud frost hardiness of Fagus crenata seedlings.Three-year-old seedlings were exposed to charcoal-filtered air or 60 nl l −1 O 3 , 7 h a day, from May to October 1999 in naturally-lit growth chambers. Half of the seedlings in each gas treatment received 250 ml of water at 3-day intervals (well-watered treatment), while the rest received 175 ml of water at the same intervals (water-stressed treatment).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…A small number of papers, however, have reported that a transitory increase in growth can be observed during the first treatment period (Rebbeck and Scherzer 2002), or as a consequence of exposure to moderate ozone concentrations . A combination of ozone and drought can exacerbate the overall effect (Alonso et al 2001;Yonekura et al 2001Yonekura et al , 2004Grulke et al 2004;Ribas et al 2005;Tausz et al 2007). Several explanations have been suggested for this behaviour, including an excessive production of reactive oxygen species (ROS) due to the concomitant action of the two stressors (Tausz et al 2007) and altered stomatal function due to ozone (stomata remain open or their closure is slowed in drought stress conditions, see Maier-Maercker 1989;McLaughlin and Downing 2002;Grulke et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…A small number of papers, however, have reported that a transitory increase in growth can be observed during the first treatment period (Rebbeck and Scherzer 2002), or as a consequence of exposure to moderate ozone concentrations . A combination of ozone and drought can exacerbate the overall effect (Alonso et al 2001;Yonekura et al 2001Yonekura et al , 2004Grulke et al 2004;Ribas et al 2005;Tausz et al 2007). Several explanations have been suggested for this behaviour, including an excessive production of reactive oxygen species (ROS) due to the concomitant action of the two stressors (Tausz et al 2007) and altered stomatal function due to ozone (stomata remain open or their closure is slowed in drought stress conditions, see Maier-Maercker 1989;McLaughlin and Downing 2002;Grulke et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…In Japan, relatively high concentrations of O 3 above 100 nl l -1 (ppb) have been frequently observed from spring to autumn in several mountainous areas (Maruta et al 1999;Aihara et al 2004;Takeda and Aihara 2007). Although limited information on the effects of O 3 on Asian forest tree species is available, several Japanese researchers have suggested that ambient levels of O 3 reduce growth and net photosynthesis of Japanese forest tree species (Izuta et al 1996;Matsumura 2001;Yonekura et al 2001aYonekura et al , 2001bYonekura et al , 2004Matsumura et al 2005). In the near future, furthermore, concentration of ground-level O 3 is expected to increase in many parts of the world, especially in Asian countries (Emberson et al 2001;Derwent et al 2002).…”
Section: Introductionmentioning
confidence: 96%
“…The O 3 concentrations were determined based on data for atmospheric O 3 obtained in the Tanzawa Mountains, where high concentrations of O 3 are detected with a mean O 3 concentration of approximately 60 ppb (Yonekura et al 2004). The chamber was 1.2 9 1.2 9 1.2 m high, with a volume of 1.73 m 3 , and was made of an aluminum framework with polyvinyl chloride sheeting on all sides except for the floor.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Takeda and Aihara (2007) examined beech saplings exposed to unfiltered air or charcoal-filtered air in an open-top chamber on the Tanzawa Mountains and reported that their total biomass was reduced considerably in the unfiltered air. As described, air pollutants such as acid fog and O 3 are common environmental stresses for beech seedlings (Shigihara et al 2008a;Yonekura et al 2004), but the effects of acid fog and O 3 have been considered separately thus far. Although few studies to date have examined the interactive effects of acid fog and O 3 on vegetation, such studies must produce more accurate predictions of future ecosystem responses to the changing environment.…”
Section: Introductionmentioning
confidence: 99%